2015
DOI: 10.4172/2157-7048.1000233
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized MWCNT and PVA Nanocomposite Membranes for Dielectric and Pervaporation Applications

Abstract: Novel PVA nanocomposite membranes were prepared with acid functionalized multiwalled carbon nanotubes (a-MWCNT) as the reinforcing material. The presence of functional groups on MWCNT is revealed by FTIR techniques. The excess swelling of poly (vinyl alcohol) (PVA) membranes were reduced by the crosslinking of glutraldehyde (GA). The functionalized MWCNT induces hydrophilicity to the PVA nanocomposites and the hydrophilic nature of the nanocomposites was revealed by the contact angle analysis. The effect of a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that the thermal, mechanical and anti-microbial properties are enhanced owing to a homogeneous distribution of silver nanoparticles. George et al [26] reported the effect of acid functionalized MWCNTs (a-MWCNTs) concentration on the dielectric and conductivity properties of the PVA/a-MWCNTs nanocomposite membranes. It was found that the conductivity properties of the PVA/a-MWCNTs membranes are increased with an increase in the a-MWCNTs loadings.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the thermal, mechanical and anti-microbial properties are enhanced owing to a homogeneous distribution of silver nanoparticles. George et al [26] reported the effect of acid functionalized MWCNTs (a-MWCNTs) concentration on the dielectric and conductivity properties of the PVA/a-MWCNTs nanocomposite membranes. It was found that the conductivity properties of the PVA/a-MWCNTs membranes are increased with an increase in the a-MWCNTs loadings.…”
Section: Introductionmentioning
confidence: 99%
“…MWCNTs has found potential applications in the photovoltatic device, sensor, nanofiller, biomedical fields, nanocomposite membrances. [19][20][21][22] Among these applications, MWCNTs are considered as the prominent nanofiller for enhancement of the conductivity, thermal stability and mechanical properties of nanocomposite membranes. [23][24][25] Many investigations indicated that the characteristics of the PVA/PVP blend can be modified by using MWCNTs.…”
mentioning
confidence: 99%